PISA DATA ANALYSIS 2018: READING DIFFICULTY LEVEL AND BULLYING TREATMENT - Safari . (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
The main objective of this study is to answer the following questions. Is there a relationship between the level of reading difficulties and the treatment of bullying based on PISA 2018. The research method used is a quantitative method. The data in this study uses PISA 2018 data which has been released to the public and has been permitted to be used for research development purposes. The population of this study is 15 year old students who are studying in 2018, while the sample is 15 year old Indonesian students taking the 2018 PISA test. The reason for choosing the sample is students who are taking the 2018 PISA test. The data in this study is in the form of a questionnaire that students answer. Indonesia, which is 11437 students. Based on the results of the regression analysis, the results showed that there was a relationship between the level of reading difficulty and bullying treatment based on PISA 2018 (P<0.000). The reliability of the instrument is 1.00 higher than the reliability of the person = 0.40. The conclusion is that statistically there is a relationship between the level of reading difficulty and bullying treatment based on PISA 2018. The higher the bullying treatment at school, the higher the students' reading difficulty level and vice versa.